Photoacoustic discrimination of antibiotic‐resistant and sensitive Staphylococcus aureus isolates. Issue 3 (23rd December 2021) - Edgar, Robert H.; Samson, Anie‐Pier; Cook, Justin; Douglas, Madeline; Urish, Ken; Kellum, John; Hempel, John; Viator, John A.
Abstract: Objectives: Bacteremia is a serious and potentially lethal condition. Staphylococcus aureus is a leading cause of bacteremia and methicillin‐resistant S. aureus (MRSA) accounts for more than a third of the cases. Compared to methicillin‐sensitive S. aureus, MRSA is more than twice as likely to be fatal. Furthermore, subpopulations of seemingly isogenic bacteria may exhibit a range of susceptibilities, often called heterogenous resistance. These heterogeneous antibiotic‐resistant infections are often misdiagnosed as hospital‐acquired secondary infections because there are no clinically used tests that can differentiate between homogeneous and heterogeneous antibiotic resistance. We describe the development and proof of concept of rapid bacterial identification using photoacoustic flow cytometry and labeled bacteriophages with the characterization and differentiation of heterogeneous antibiotic‐resistant bacterial infections. Methods: In photoacoustic flow cytometry, pulsed laser light is delivered to a sample flowing past a focused transducer and particles that absorb laser light create an acoustic response. Optically labeled bacteriophage are added to a bacterial mixture that flows through the photoacoustic chamber. The presence of target bacteria is determined by bound labeled phage which are detected photoacoustically. Incubation of bacterial samples in the presence and absence of the antibiotic daptomycin creates a difference in bacterial cell numbers that is quantified using photoacoustic flow cytometry. Results: Four clinical isolates were tested in the presence and absence of daptomycin. Photoacoustic events for each isolate were recorded and compared to growth curves. Samples treated with daptomycin fell into three categories: resistant, susceptible, and heterogeneous resistant. Conclusions: Here we show a method to determine the presence of bacteria as a marker for bloodstream infection level and antibiotic sensitivity in less than 4 hours. Additionally, these results show an ability to identify heterogeneous resistant strains that are often misidentified.